Israeli Mizrahi Feminist Activism Beyond Intersectional Struggles: From National to Multicultural Challenges - Daniele, G. (CIEG International Congress "Gender Studies in Debate: Pathways, Challenges and Interdisciplinary Perspectives", 2019)
As part of my ongoing research project, this paper aims to draw attention to the way through which Mizrahi women activists have been part of the Israeli feminist movement itself but, at the same time, the majority of them have been marginalised from the mainstream (Dahan-Kalev 2001; Lavie 2011, 2014; Shiran 1991). As a result, Mizrahi feminist activists have attempted to create alternative forms of grassroots politics and everyday resistance. By calling into question the asymmetric relations between Ashkenazim and Mizrahim within Israel, the Mizrahi feminist outlook has stressed the importance to address the needs of women who live in marginalised socio-economic conditions and suffer both individual oppression because of their gender and collective oppression for belonging to underprivileged communities. As one of the most significant cases of Mizrahi feminist activism, since the late 1990s the organisation called Achoti (Sister) - for women in Israel has dealt with the meaning of sisterhood in multiethnic and multicultural societies. Founded in south Tel Aviv, and following the principles of “feminism of colour”, they have represented an alternative way of looking at and questioning Israeli society. By deeply connecting women from very different ethnic and socio-political backgrounds, they have united common struggles led by the poorest and most underrepresented communities in Israel. As underlined by their multi-ethnic, multi-national and feminist agenda, women activists coming from underprivileged communities inside Israel have a mutual interest in struggling together, for everything, for ending the occupation, for ending gentrification, for demanding justice and equal distribution of funds. This can be considered as a challenging field of study needing to be analysed more in depth and related to the main subject matters concerning several other forms of feminist activism across the world.